Solid-State Drawing of Commercial Poly(Lactic Acid) (PLA) Based Filaments - Walker, Julian (2019)
In the present work, solid-state drawing of commercial PLA-based extruded filamentswas investigated. Two different filaments were used: one based on neat PLA and theother based on PLA filled with copper particles. The effect of the processing parameterssuch as the drawing temperature and the draw ratio on the materials morphology andthermal and mechanical behavior was analyzed. A specially designed device whichsimulates the solid-stated drawing stage frequently used for fibers manufacturing wasapplied. The drawing effects were evidenced by the results of the degree of crystallinityand tensile parameters, as well as by SEM analysis and topographical observations ofthe surfaces of the filaments. From these results, it was concluded that the draw ratiois more important than the drawing temperature as a determining factor of the tensileperformance of the PLA-based filaments investigated. However, the drawing temperatureplays a key role to establish the critical draw ratio to obtain stable solid-state drawing.